Educational Quality Assurance Systems as a Strategy for Improving the Quality of Educational Institutions: A Literature Review - Yunita Endra Megiati; Noor Komari Pratiwi; Syafa’atun Syafa’atun; Rizki Rizkyatul Basir (SEAN Institute, 2026)
Educational quality is a major determinant of national competitiveness in the global era. To respond to this challenge, educational institutions are required not only to provide education but also to ensure that educational processes are implemented effectively, efficiently, and in accordance with established quality standards. In this context, an educational quality assurance system serves as a strategic approach to ensuring that educational processes consistently meet predetermined standards. This article aims to comprehensively examine the concepts, principles, and implementation of educational quality assurance systems as a strategy for improving the quality of educational institutions. This study employs a literature review method by analyzing various reputable scientific sources, including international journal articles, academic books, and relevant educational policy documents. The literature search was conducted through scientific databases such as Scopus, Web of Science, and Google Scholar using keywords focused on quality assurance and educational quality management. The findings indicate that quality assurance systems play a crucial role in improving institutional quality through three main pillars: the implementation of rigorous quality standards, continuous evaluation mechanisms, and the development of a strong quality culture across all organizational elements. The effectiveness of quality assurance implementation depends not only on formal procedures but also on visionary leadership, the active participation of the entire academic community, and a strong commitment to the principle of continuous quality improvement. This principle enables educational institutions to adaptively improve curricula, learning processes, and organizational governance in response to changing stakeholder needs. Therefore, educational quality assurance systems constitute a strategic instrument that not only strengthens internal quality but also enhances institutional competitiveness at the global level.